Fear of pain and movement in a patient with musculoskeletal chronic pain - Raudenska, Jaroslava; Javurkova, Alena; Kozak, Jiri (Neuro endocrinology letters, 2013)
Pain-related fear may pose a serious barrier in the management of patients with chronic musculoskeletal pain, resulting in severe functional impairment in many cases. The paper describes the cognitive-behavioural therapy of a patient with a specific phobia (fear of pain and movement). The principal objective of the therapy was to educate the patient in strategies and skills to manage his fear and to verify the effect of the therapy. Both group and individual therapy was used. Group multimodal therapy of pain was provided by an interdisciplinary team of health care providers, specialising in pain management (psychotherapist, doctors and physiotherapists). The programme was based on operant therapy principles and included pacing and graded exercising and walking, relaxation, group education about ergonomics, and fear and pain relapse prevention. Reduction in the fear of pain and movement was achieved, and social bonds and physical and social activities improved after the psychotherapy, while the results were stable for two years.
Keywords: Social Behavior; management bolesti; Chronic Pain; Male; Treatment Outcome; Pain Management; kognitivně behaviorální terapie; Musculoskeletal Pain; Cognitive Behavioral Therapy; mužské pohlaví; Adult; dospělí; sociální chování; Fear; výsledek terapie; lidé; Humans; muskuloskeletální bolest; chronická bolest; strach